Характер наследования количественного содержания 7S и 11S глобулиновых белков у гибридов F₃ семян сои - Адамовская, В.Г.; Молодченкова, О.О.; Сичкарь, В.И.; Картузова, Т.В.; Безкровная, Л.Я.; Лаврова, Г.Д. (Фактори експериментальної еволюції організмів, 2013)
Aims. The major components of soybean seed proteins are 11S globulin (glycinin) and 7S globulin (ȕ-
conglycinin), which are storage proteins that account for 70 % of the total seed protein. For estimation the
biotypes of soybean, excelling initial varieties for protein’s quality, the contents and 11S globulins/7S globulins
ratio, the character of inheritance of 11S globulins and 7S globulins contents at the F3 hybrids of soybean
seed were studied. Methods. Contents of protein were measured according to the Kjeldahl method. 7S and
11S globulins were separated by method, which was developed in the Laboratory of Plant Biochemistry
(Patent # 42181). Results. It was established, that contents of 11S globulins at the F3 hybrids is mainly inher-
6
ited on the type of prevailing of parent with low contents of 11S globulins (hp from -0,25 to -2,3), and 7S
globulins – on the intermediate type of inheritance with deviation to parent with best on contents of 7S
globulins (hp from +0,076 to +0,69). Nevertheless, among the studied hybrid combinations there are hybrids,
where the effect of prevailing of the best parent on the contents of these indexes is marked (hp from +2,0 to
+2,1). Conclusions. The got results testify that contents of 7S and 11S globulins in the soybean seed at the F3
hybrids is controlled by the difficult genetic system with the different type of genes action and cooperation.